Sustainable Leadership and Customer-Oriented Culture Drive Employee Performance Excellence - Aan Suhaemi (Harmony Management: International Journal of Management Science and Business, 2025)
This study investigates the influence of sustainable leadership and customer-oriented culture on employee performance at PT Krakatau Sarana Properti (PT KSP), a subsidiary of PT Krakatau Steel operating in Indonesia’s commercial property sector. Amid rapid globalization and technological change, organizations are compelled to foster adaptive cultures and leadership approaches that ensure both operational excellence and long-term sustainability. Drawing on Organizational Behavior and the Resource-Based View, this research positions sustainable leadership as a strategic resource that not only directly enhances employee performance but also shapes a customer-oriented culture—an intangible asset vital for organizational competitiveness. Employing a quantitative, explanatory research design, data were collected from 95 employees using a structured questionnaire and analyzed with Structural Equation Modeling-Partial Least Squares (SEM-PLS). The findings reveal that sustainable leadership has a significant positive impact on employee performance and customer-oriented culture. Additionally, customer-oriented culture exerts a strong influence on employee performance and partially mediates the relationship between sustainable leadership and employee performance. These results underscore the importance of integrating sustainability principles into leadership practices and embedding customer-centric values throughout the organization. The study provides both theoretical and practical contributions, offering a more holistic understanding of how sustainable leadership and organizational culture jointly drive superior performance. For PT KSP and similar organizations, investing in sustainable leadership development and cultivating a customer-oriented culture are recommended strategies to enhance employee motivation, adaptability, and long-term competitive advantage in a dynamic business environment.